Effect of post-activation potentiation by combining heavy squats and sprints on the countermovement long jump (Pilot study) - Králová, Tereza; Vanderka, Marián; Cacek, Jan; Matura, Matěj; Popelka, Filip (Studia Sportiva, 2018)
Weightlifting heavy load exercises are commonly used as a key instrument for enhancing performance if compared to those not using the exercise stimulating muscle tone. Studies examined the post-activation effect (PAP) using only one parameter but not in consecutive and intermingling exercises to prolongated the time of the PAP effect duration and maintain increased performance. Nine male students, with resistance training experience, performed warm-up and exercises enhancing muscle tone (EEMT) using squats to 90° flexion in the knee joint with 80 % 1 RM (repetition maximum) in 3 sets with 3 repetitions of squat in each set (2-3 min. rest intervals). After EEMT they performed a 10-m sprint test in 2nd and 5th min, the countermovement long jump (CLJ) test in the 5th and 6th minute, a 10-m sprint test in the 10th and 11th minute and the CLJ test in the 12th and 14th minute. The results showed that the average improvement was in 10-m sprint after EEMT 0,013 ± 0,05 seconds, but there were no statistical differences observed between the result without and with EEMT (p>0.05). We observed a significant improvement between jumps without and with EEMT in 5 – 14th min (p<0.05). There were no statistical differences between the results in CLJ carried out in 5-6th min after EEMT and after two 10-m sprints and the results carried out in 12-14th min. after EEMT, four 10-m sprints and two jumps (p>0.05). It was found that 10-m sprint has no negative effect on performance in the long jump and could be regularly applied to prolong the PAP effect.
Keywords: Athletic Performance; sportovní výkon; sportovci; Athletes; Humans; Running; dřep; lidé; běh